Lecturers' views on plagiarism and practices to help students to avoid plagiarism - Ross Ardiana, Mohd Ali (Universiti Malaysia Sarawak (UNIMAS), 2009)
Plagiarism is a crucial issue in all areas of education regardless in school or institution of higher learning. A survey was conducted on UNIMAS lecturers to investigate their views on plagiarism and practices to help and educate students to avoid plagiarism.The following research objectives were investigated namely; (i) number of plagiarism cases handled by UNIMAS lecturers within the last two years, (ii) types of plagiarism committed by students, (iii) methods used by the lecturers to detect plagiarism in students’ assignment, (iv) actionstaken against students who plagiarized other’ works, and (v) practices employed by the lecturers to help students to avoid plagiarism. An adapted questionnaire was administered to 348 UNIMAS lecturers in nine faculties including the Centre for Language Studies. Analysis of data was done quantitatively which frequency and percentage of the data collected were calculated. The findings of the study revealed that 42 participants (45.2 %) dealt with less than five students’ plagiarized works within the last two years or last four semesters. Besides, 50 participants (76%) stated that the most reported type of plagiarism was The Photocopy (the writer copies significant portions of text straight from a single source, without alteration). The findings of this study also indicated that majority of lecturers chose manual detection method rather than available electronic detection technology or service . In addition to that, 50 participants (76%) reported that students should be given second chance. It was indicated by their option of ‘give an advice or a warning’ to students if they found plagiarism in the students’ work as it also works to inform students who committed plagiarism out of ignorance. Lastly, 52 participants (80%) chose to make the consequences of plagiarism clear to students as the main approach to help students to avoid plagiarism. One of the implications from the study suggests that each effort or practice taken by the lecturers to help students to avoid plagiarism must closely address the types of plagiarism committed by them.Generally, the effort in educating students to avoid plagiarism should focus on writing skill as well as making appropriate citation, paraphrasing, and summary of the sources used.